Fenomenul fascist în viziunea teoreticienilor marxiști (The Fascist Phenomenon Viewed by Marxist Theorists) - Sabin DRĂGULIN (Polis: Revista de Stiinte Politice, 2015)
The author of this historiographical study aims to present some of the most interesting Marxist authors’ theses that have analysed the fascism in the interwar period. The goal of this research is to offer, through these visions a better understanding over those theses following the need to identify the nature of the ideological struggle between the communism and the fascism